Polymer-based shielding approaches as a practical solution reducing radiological risks in field operations - Lucas Rodrigues; Claudio Antonio Federico; Tercio Brum; Sergio Gavazza; Jéssica de Moutta Gomes; Edson Ramos de Andrade (Brazilian Journal of Radiation Sciences, 2024)
The objective of this research is to evaluate various polymeric materials that have the potential to serve as substitutes or supplements to heavy vehicle structures for radiation-intensive environments. The materials under investigation include Nylon 6 (PA-6, C6H11NO), polyethylene (PE, C2H4), polypropylene (PP, C3H6), polyvinyl chloride (PVC, C2H3Cl), and polymethylacrylate (PMMA, C5H8O2). This study's primary aim is to determine each material's effectiveness in shielding against radiation and reducing exposure to vehicle occupants. As a new approach, this research examines the impact of utilizing polymeric materials and the potential health hazards for young drivers of both sexes, such as developing solid cancers from radiation exposure. According to the study, PVC was the most efficient polymer with a Transmission Factor (TF) of 0.44, leading to a 56% decrease in the relative risk estimate for the maximum thickness evaluated (20 cm). On the other hand, PP was identified as the least efficient, with a TF of 0.65, resulting in a 35% reduction in the relative risk estimate for the same thickness. The study concludes that each polymer has varying degrees of attenuation and that combining their properties is essential to achieving the desired level of risk reduction.